Correlation between Formic Acid Oxidation and Oxide Species on Pt(Bi)/GC and Pt/GC Electrode through the Effect of Forward Potential Scan Limit - Jelena D. Lović (Journal of Chemistry)
Following earlier works from our laboratory, further experiments on electrochemical behavior in formic acid oxidation at electrodeposited Pt(Bi)/GC and Pt/GC electrode were performed in order to examine the effect of successive increase of the forward potential scan limit. Correlation between formic acid oxidation and oxide species on Pt(Bi)/GC electrode with increases of forward potential scan limit is based on the dependency of the backward peak potential from backward peak current. The obtained dependency reveals Bi influence for the scan limits up to 0.8 V. Since the Pt(Bi)/GC electrode is composed of Bi core occluded by Pt and Bi-oxide surface layer, the observed behavior is explained through the influence of surface metal oxide on easier formation of OHad species. Nevertheless, the influence of electronic modification of Pt surface atoms by underlying Bi is present and leads to the stronger adsorption of OH on Pt. At higher forward potential scan limits (from 0.8 V), Pt has a dominant role in HCOOH oxidation.